Korpus og seddelarkiv, fredelig sameksistens mellom det beste og det gode? - Ore, Christian-Emil (Nordiske Studier i Leksikografi, 1995)
This paper focuses on how to save the information in a traditional citation archive for the computerized world. The sample archive is a citation archive at the Department of Lexicography at the University of Oslo, Norway. Originally the archive was to be keyed and given a SGML markup. Due to reasons discussed in the paper this approach was abandoned. The archive is now converted into a indexed facsimile data base which seems to be a better solution both from a scientific and from an economic point of view. The research, the program development and the actual con vers ion of the information in the archive forms a sub project of the Documentation project, which is a collaboration between the four Norwegian universities.